Dukun Dalam Perspektif Kitab Al-Halal Wal Haram Fi Al-Islami - Fikri Hailal; Zulkipli Lessy; Siti Nuroh (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2023)
This article departs from the phenomenon of shamanism and legal perceptions of shamanic practices in Islam which are often found in people who still adhere to occult beliefs, and even become content or broadcasts in cyberspace. The aim to be conveyed in this article is to provide a legal perception of the practice of shamanism and present actions that counter occult matters, so that human monotheism is maintained by providing an understanding of how the Al-Qur'an perspective views shamanism and punishes shamanism without castrate the original law. In Arabic, shamans are called: kahana means supernatural predictions, fortune-tellers or priests; old rags; worn; junkman, rags; ugly and disgusting in appearance; witch doctor. The approach used in this study is the sociology of knowledge, Karl Manheim. By using a qualitative method of content analysis. Thus, the findings obtained, shamanism in the book Al-Halal Wal Haram Fi Al-Islami is an act of claiming to know about unseen knowledge, such as informing that something will happen on earth by relying on a cause, and the law of shamanism in Islam is permissible, if it is conceptualized in 'alal birri wattaqwa wa tanha 'anil fakhsak wal munkar and unlawful if it is conceptualized in the direction of polytheism, evil, and even heinous acts.